Perspectives on choosing Islamic insurance services in Thailand - Labduang, Abbas; Noipom, Tawat (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The Islamic insurance business in Thailand has tremendous growth potential. However, the market penetration of Islamic insurance is still relatively low. Therefore, it is necessary to examine the factors of choosing Islamic insurance services in Thailand. The purpose of this study was to study the in-depth understanding of perception and comprehension, adherence to religious principles and integrated marketing communication in Islamic insurance in Thailand by using an in-depth interview method. Data were collected from 10 key informants from (1) executives and (2) Islamic insurance members who were selectively selected. There were 3 types of data collection in this study 1) in-depth interviews, 2) observations, and 3) note-taking. Data were analyzed using content analysis; classified the information and analyzed each point. The results of the study confirmed that there are three important factors for choosing Islamic insurance services in Thailand: (1) perception and understanding; a good understanding will result in increased demand for Islamic insurance products and services, (2) adherence to religious principles; Islamic insurance products are compliant with Shariah principles and have no prohibited components in Islam will increase customers’ demand and (3) integrated marketing communications in Islamic insurance; media communication or words of mouth method is a significant way to attract customers. Last, Islamic marketing should focus on equality and social well-being of people in society.